Final answer:
To write the equation in vertex form, y = a(x - h)^2 + k, we need to complete the square. Given the equation y = 8(x + )^2 + , we can find the value of h by taking half of the coefficient of x and squaring it. Similarly, the value of k can be found by substituting the value of h into the equation and simplifying. Therefore, the equation in vertex form is y = 8(x + 1/2)^2 + 0.
Step-by-step explanation:
To write the equation in vertex form, y = a(x - h)2 + k, we need to complete the square.
Given the equation y = 8(x + )2 + , we can find the value of h by taking half of the coefficient of x and squaring it. Since the coefficient of x is 1, half of it is 1/2. So h = 1/2.
Similarly, the value of k can be found by substituting the value of h into the equation and simplifying. In this case, since there is no constant term after the squared term, k = 0.
Therefore, the equation in vertex form is y = 8(x + 1/2)2 + 0.